1987
DOI: 10.1152/jappl.1987.63.1.322
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of hypertension and chronic running program on rat heart

Abstract: Previous studies in hearts of female rats have demonstrated that ventricular hypertrophy due to systolic overload, when combined with hypertrophy induced by a chronic swimming program, results in increased cardiac performance and enhanced contractile protein activity compared with the effects of hypertension alone. To explore how a chronic running program affects the function of hypertensive hearts, renal hypertension was created in female rats, and the animals were subjected to a program of chronic treadmill … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Our findings give support to the improvement of left ventricular performance demonstrated in exercised SHR isolated heart (5,17,19). Although we did not measure cardiac function in the present study, the morphological and mechanical cellular adaptations reported here may contribute to our understanding of the mechanisms underlying the benefits of exercise training on the cardiac function of SHR (i.e., improved left ventricular performance).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our findings give support to the improvement of left ventricular performance demonstrated in exercised SHR isolated heart (5,17,19). Although we did not measure cardiac function in the present study, the morphological and mechanical cellular adaptations reported here may contribute to our understanding of the mechanisms underlying the benefits of exercise training on the cardiac function of SHR (i.e., improved left ventricular performance).…”
Section: Discussionsupporting
confidence: 80%
“…There is evidence at the whole heart level that exercise training provides beneficial adaptations to cardiac contractile function and morphology in hypertensive rats (5). Nevertheless, to date the effects of exercise training and detraining on the left ventricular single myocyte morphological and mechanical properties of SHR are not known.…”
mentioning
confidence: 99%
“…The LVW/BW, LV end-diastolic dimension, and velocity-time integral of aortic ejection flow increased, without an increase in cardiomyocytes width as previously reported. 12,13 This is the first report that shows the involvement of calcineurin in physiological adaptive hypertrophy. The role of calcineurin in cardiac hypertrophy had not yet been elucidated.…”
Section: Discussionmentioning
confidence: 93%
“…myocardium; tension-pCa; endurance training; contractility CHRONIC ENDURANCE EXERCISE training has been shown to elicit positive adaptations in the cardiovascular system that result in improved performance at maximal and submaximal work levels. Among these adaptations is a training-induced increase in peak left ventricular pressure development (5,10,27,28). Because pressure development in the ventricle is driven by the capacity of the myocardium to generate tension or force, much work has been focused on the effect of exercise training on myocardial force generation.…”
mentioning
confidence: 99%